Mensch, Maschine! Ein unplugged-Einstieg in KI und maschinelles Lernen. - Opel, Simone; Nordemann, Lina; Schulte, Carsten; Tenberge, Claudia (Merz Medien + Erziehung. Zeitschrift für Medienpädagogik.)

Organic Light‐Emitting Diodes Based on a Columnar Liquid‐Crystalline Perylene Emitter - Keum, Changmin; Becker, David; Archer, Emily; Bock, Harald; Kitzerow, Heinz-Siegfried; Gather, Malte C.; Murawski, Caroline (Advanced Optical Materials)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Dynamics of a liquid crystal-based modulator with germanium substrates for mid-infrared radiation - Risse, Anna Margareta; Schmidtke, Jürgen; Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Einstellungen von Kindern gegenüber Schülerinnen und Schülern mit einem sonderpädagogischen Förderbedarf im Zusammenhang mit dem Vorbildverhalten ihrer Eltern. Vortrag auf der 8. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF). Thema: „Bildung gestalten – Partizipation erreichen – Digitalisierung nutzen“ - Löper, Marwin Felix; Hellmich, Frank; Hoya, Fabian Karl

Pre-service teachers’ cooperation and children’s social participation in inclusive primary schools. Single Paper. EARLI SIG 15 Biennial Conference 2020 `Special Educational Needs´. “Learning difficulties and inclusion: Challenges (and solutions) for the future” - Hoya, Fabian Karl; Schulze, Jan Roland; Hellmich, Frank; Schwab, Susanne; Blumberg, Eva

Familie und verantwortete Elternschaft - Landhäußer, Sandra (Handbuch Familie. Bildung, Erziehung und pädagogische Arbeitsfelder)
Das Handbuch Familie repräsentiert den theoretischen und empirischen Stand der Familienforschung aus konsequent interdisziplinärer Sicht. Mit dem Schwerpunkt auf die Themen Bildung und Erziehung und dem Bereich, der Familienarbeit in sozialpädagogischen Arbeitsfeldern bedeutet, bietet der Band die komplette Bandbreite Diskurses ab. In der neu konzipierten Struktur wird ein umfassendes Bild von Familie als einer pädagogischen Institution gezeichnet, in das die aktuellen wissenschaftlichen Erkenntnisse und Forschungsergebnisse einfließen.
Keywords: ng Armut Familientherapie Rechtsextreme Familen

Ambivalenzen der Förderung. Erziehungs- und Lernbegleitung für Kinder, Jugendliche und junge Erwachsene durch studentische Mentorinnen und Mentoren - Beerheide, N.; Dopheide, F.; Freitag, Christine; Koch, L.; Struchholz, C.; Westphal, Petra (Emotionale und soziale Entwicklung in der Pädagogik der Erziehungshilfe und bei Verhaltensstörungen)

Das Theater der Zärtlichkeit. Affektkultur und Inszenierungsstrategien in Tragödie und Komödie des vorbürgerlichen Zeitalters

Organische Chemie - Andexer, Jennifer N.; Beifuss, Uwe; Beuerle, Florian; Brasholz, Malte; Breinbauer, Rolf; Ernst, Martin; Greb, Julian; Gulder, Tobias; Hüttel, Wolfgang; Kath‐Schorr, Stephanie; Kordes, Markus; Lehmann, Matthias; et al. (Nachrichten aus der Chemie)
Keywords: General Chemical Engineering; General Chemistry

Erbium-Catalyzed Regioselective Isomerization–Cobalt-Catalyzed Transfer Hydrogenation Sequence for the Synthesis of Anti-Markovnikov Alcohols from Epoxides under Mild Conditions - Liu, Xin; Longwitz, Lars; Spiegelberg, Brian; Tönjes, Jan; Beweries, Torsten; Werner, Thomas (ACS Catalysis)
Keywords: Catalysis; General Chemistry

Benzoxepinones: A new isoform-selective class of tumor associated carbonic anhydrase inhibitors - Grandane, Aiga; Nocentini, Alessio; Werner, Thomas; Zalubovskis, Raivis; Supuran, Claudiu T. (Bioorganic and Medicinal Chemistry)
Keywords: Organic Chemistry; Clinical Biochemistry; Drug Discovery; Pharmaceutical Science; Molecular Biology; Molecular Medicine; Biochemistry

Plasma‐Assisted Immobilization of a Phosphonium Salt and Its Use as a Catalyst in the Valorization of CO 2 - Hu, Yuya; Peglow, Sandra; Longwitz, Lars; Frank, Marcus; Epping, Jan Dirk; Brüser, Volker; Werner, Thomas (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Stereoselective Synthesis of a cis-Cedrane-8,9-diol as a Key Intermediate for an Amber Odorant - Stefanow, Vivian; Grandane, Aiga; Eh, Marcus; Panten, Johannes; Spannenberg, Anke; Werner, Thomas (Organic Process Research and Development)
Keywords: Organic Chemistry; Physical and Theoretical Chemistry

Selective Construction of C−C and C=C Bonds by Manganese Catalyzed Coupling of Alcohols with Phosphorus Ylides - Liu, Xin; Werner, Thomas (Advanced Synthesis and Catalysis)
Keywords: General Chemistry

Catalytic, Kinetic, and Mechanistic Insights into the Fixation of CO2 with Epoxides Catalyzed by Phenol‐Functionalized Phosphonium Salts - Hu, Yuya; Wei, Zhihong; Frey, Anna; Kubis, Christoph; Ren, Chang‐Yue; Spannenberg, Anke; Jiao, Haijun; Werner, Thomas (ChemSusChem)
Keywords: General Energy; General Materials Science; General Chemical Engineering; Environmental Chemistry

Information asymmetry and the SEC framework in digital markets - On the role of reputation systems in alleviating buyers' skepticism and inducing their willingness to pay - Bellouchi, Houda

Standort, Perspektive und Haltung: Überlegungen zum Proprium der Kirchengeschichte als einer Disziplin theologischer Wissenschaft - Schmidt, Jochen (Kirchengeschichte)
Keywords: Kirchengeschichte; Theologie

FLP-catalysis meets hydrogen-bond activation - Sitte, Nikolai A.; Köring, Laura; Roesky, Peter W.; Paradies, Jan (Organic & Biomolecular Chemistry)
The potential of two chiral amidines and three non-chiral boranes in the metal-free hydrogen activation was explored.

Dually Crosslinked Supramolecular Hydrogel for Cancer Biomarker Sensing - Li, Jie; Ji, Chendong; Lü, Baozhong; Rodin, Maksim; Paradies, Jan; Yin, Meizhen; Kuckling, Dirk (ACS Applied Materials & Interfaces)

Palladium‐Catalyzed Polycondensation for the Synthesis of Poly(Aryl)Sulfides - Hou, Peng; Oechsle, Peter; Kuckling, Dirk; Paradies, Jan (Macromolecular Rapid Communications)